PENGARUH TINGKAT PENDIDIKAN, PENGETAHUAN AKUNTANSI DAN PELATIHAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI DIMODERASI KETIDAKPASTIAN LINGKUNGAN USAHA KECIL MENENGAH - Hudha, Choirul (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
The purpose of the study were to examine and analyze the influence of education level, accounting knowledge, accounting training on the use of accounting information, and to examine and analyze the environmental uncertainty as a moderating variable that influence the education level, accounting knowledge and accounting training on the use of accounting information. The number of population in this research were 514 owners of Small and Medium Enterprises (SMEs) in Surabaya. The sample selection in this research based on proportional random sampling and choosen 225 owners of the SMEs. The data collection techniques used questionnaires, interviews, and documentation. The analyze method used Structural Equation Modelling (SEM). The results showed that the education level did not significantly influence the use of accounting information. The accounting knowledge and accounting training significantly influence the use of accounting information on SMEs. The environmental uncertainty as a moderating variable moderated the influence of education level, accounting knowledge, and accounting training on the use of accounting information